Másik Magyarország - Dénes, Nagy (Hungary : László, Sára ; Gerő, Marcell, 2013)
Ten years ago, Imre Bukta, one of the leading figures of contemporary Hungarian art scene, decided to move back to his remote home village of Mezőszemere in Heves county. His goal was to create an opportunity, both for himself and for the village community, to find some kind of renewal. Another Hungary is a blueprint of this search for a new identity, a detailed analysis of the present situation: what has been achieved so far? What is out there, and what can be done? Irony, humor and absurdity shape the harsh reality of a traditional community where modernization resulted in the loss of cultural traditions and economic stability, leaving a void and nothing to fill it with.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films